Sunscreen products impair the early developmental stages of the sea urchin Paracentrotus lividus - Cinzia Corinaldesi (Nature Portfolio, 2017)
Abstract Marine ecosystems are increasingly threatened by the release of personal care products. Among them, sunscreens are causing concern either for the effects on skin protection from UV radiation and for the potential impacts on marine life. Here, we assessed the UVA protective efficacy of three sunscreens on human dermal fibroblasts, including two common products in Europe and USA, and an eco-friendly product. The sunscreens’ effects were also tested on Paracentrotus lividus, a marine species possibly threatened by these contaminants. We found that all tested sunscreens had similar efficacy in protecting human fibroblasts from UVA radiation. Conversely, the sunscreens’ effects on embryo-larval development of P. lividus were dependent on the product tested. In particular, the USA sunscreen, containing benzophenone-3, homosalate and preservatives, caused the strongest impact on the sea urchin development, whereas the eco-friendly sunscreen determined the weakest effects. These results suggest that although the tested products protected human skin cells from UVA-induced damage, they might severely affect the success of recruitment and survival of the sea urchin. Our findings underline the importance of developing eco-friendly sunscreens for minimising or avoiding the impact on marine life while protecting human skin from UV damage.